Stability of Fractional Differential Equations without Singular Kernal - Harikrishnan, S.; Kanagarajan, K.; Vivek, D. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we establish four types of Ulam stability, namely Ulam-Hyers stability, generalized Ulam-Hyers stability, Ulam-Hyers-Rassias and generalized Ulam-Hyers-Rassias stability for differential equation of fractional order.